Réponses

2013-05-06T18:35:06+02:00

A=7-1x x+( -1) x y - (-1) x 2

A=7- x + (-y) + 2

A= 7-x-y+2

 

B= 5+ 1x 4x + 1 x 5

B=5+ 4x+5

 

C=[-1 x (-5a) + (-1) x 3] + 4

C=5a-3+4

 

D=(4a+5b)+ 1 x 2a + 1 x b

D= 4a+5b+ 2a+b

2013-05-06T18:44:05+02:00

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

a= 7-(x+y-2)

a=7-x-y+2

a=7+2-x-y

a=9-x-y

a=9-x-y

 

 

 b=5+(4x+5)

 

  b=5+4x+5 

 

 b5+4x+5

b=5+5+4x

b=10+4x

 

 

 

c= -(-5a+3)+4

c=+5a-3+4

c=+5a+1

 

 

 d=(4a+5b)+(2a+b)

d=4a+5b+2a+b

d=4a+2a+5b+b

d=6a+6b

voila je pense que c'et ça bon courage!!!